Evaluating the Brewer–Dobson circulation and its responses to ENSO, QBO, and the solar cycle in different reanalyses - Jian Rao; YueYue Yu; Dong Guo; ChunHua Shi; Dan Chen; DingZhu Hu (Earth and Planetary Physics, 2019)
This study compares the climatology and long-term trend of northern winter stratospheric residual mean meridional circulation (RMMC), as well as its responses to El Niño-Southern Oscillation (ENSO), stratospheric Quasi Biennial Oscillation (QBO), and solar cycle in ten reanalyses and a stratosphere-resolving model, CESM1-WACCM. The RMMC is a large-scale meridional circulation cell in the stratosphere, usually referred to as the estimate of the Brewer Dobson circulation (BDC). The distribution of the BDC is generally consistent among multiple reanalyses except that the NOAA twentieth century reanalysis (20RC) largely underestimates it. Most reanalyses (except ERA40 and ERA-Interim) show a strengthening trend for the BDC during 1979–2010. All reanalyses and CESM1-WACCM consistently reveal that the deep branch of the BDC is significantly enhanced in El Niño winters as more waves from the troposphere dissipate in the stratospheric polar vortex region. A secondary circulation cell is coupled to the temperature anomalies below the QBO easterly center at 50 hPa with tropical upwelling/cooling and midlatitude downwelling/warming, and similar secondary circulation cells also appear between 50–10 hPa and above 10 hPa to balance the temperature anomalies. The direct BDC response to QBO in the upper stratosphere creates a barrier near 30°N to prevent waves from propagating to midlatitudes, contributing to the weakening of the polar vortex. The shallow branch of the BDC in the lower stratosphere is intensified during solar minima, and the downwelling warms the Arctic lower stratosphere. The stratospheric responses to QBO and solar cycle in most reanalyses are generally consistent except in the two 20CRs.